Steady analyses of potassium stable isotopes using a Thermo Scientific Neoma MC-ICP-MS. Issue 6 (29th April 2022) - Télouk, Philippe; Albalat, Emmanuelle; Tacail, Théo; Arnaud-Godet, Florent; Balter, Vincent
Abstract : Potassium stable isotope compositions exhibit a wide range of natural variation (∼3‰), whose measurement has been recently achievable thanks to the development of collision cell, XHR mode, cold and dry plasma, or dummy bucket MC-ICP-MS. Abstract : Potassium stable isotope compositions ( 41 K/ 39 K ratio) exhibit a wide range of natural variation (∼3‰), whose measurement has been recently achievable thanks to the development of various methods, including collision cell, XHR mode, cold and dry plasma, or dummy bucket MC-ICP-MS. Here, we report the capabilities of a Thermo Scientific new generation MC-ICP-MS, Neoma, to routinely measure the 41 K/ 39 K ratio. We found that the effect of potassium concentration mismatch between the sample and standard is comparable to other reported methods. However, the effect of acid concentration mismatch is not perceptible from 0.05 M to 0.5 M HNO3, and the effect of matrix elements on the accuracy of sample-standard bracketing measurements is lower compared to other reported methods up to the element-K normalized ratio of >15%. This relative insensibility to non-spectral matrix effects most probably results from the new design of the introduction system that integrates an iCAP Qnova Series ICP-MS torch and injector assembly. The resulting repeatability (or short-term external precision) and long-term intermediate precision (or long-term reproducibility) are 0.06‰ (2SD, n = 55) and 0.07‰ (2SD, n = 12), respectively. We then use a very simple one step chemical purification of K by ion exchange chromatography and apply the method to the measurement of the δ 41 K value of geological and biological reference materials, and blood samples of cancer and control patients. The results for reference materials show very good agreement with previously reported values and extend the available data for future interlaboratory comparison studies. Blood samples of cancer and control patients exhibit similar δ 41 K values despite a suspected isotopic difference between tumour and normal tissues. The overall instrumental robustness observed using the XHR mode remains to be challenged with the precell mass filter and hexapole collision/reaction cell upgrade.